A Legal Review of the Use of the “Gudang Baru” Trademark as an Alleged Infringement and Unfair Competition Against Gudang Garam - Sarah Tyas Prameswari; Revima Nelyna Muntaha; Laila Nur Fadila; Ikhwan Aulia Fatahillah (Anthroposia: Journal of Social and Human Development, 2026)
This study examines the legal implications of the use of the “Gudang Baru” trademark as an alleged trademark infringement and form of unfair competition against the well established “Gudang Garam” trademark within the Indonesian legal system. The research adopts a non empirical normative juridical approach based on statutory analysis, case analysis, and conceptual legal reasoning. Primary legal materials consist of international intellectual property instruments, national trademark legislation, competition law regulations, trademark registration rules, and judicial decisions relevant to the dispute. The findings indicate that the legal assessment extends beyond visual similarity and requires consideration of consumer confusion, the protection of well known trademarks, good faith registration requirements, and broader principles of market fairness. The study further demonstrates that the status of Gudang Garam as a well known trademark strengthens its entitlement to enhanced legal protection under domestic and international legal frameworks. The analysis also reveals that the use of the Gudang Baru trademark raises concerns regarding passing off, free riding, and bad faith registration that may distort fair competition. Stronger integration between trademark law and competition law is necessary to preserve legal certainty, protect commercial goodwill, and promote equitable market competition.